Implementasi Metode Design Thinking Dalam Pembuatan Prototype Aplikasi Rental Mobil Berbasis Website - Sandhiprasta, I Putu Riyan; Astuti, Luh Gede (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022DO - 10.24843/JNATIA.2022.v01.i01.p26, 2022)
Today’s means of transportation have become an important need in society, to support all activities that require adequate mobility. Moreover, four wheeled transportation is more convenient to use on the road . Car rental service companies are the solution for these problems. The increasing competition in car rental services requires an innovation in utilizing information and technology in the marketing process in order to be different and superior to other competitors. The method used in this research is the Design Thinking method. Design Thinking method that aims to be able to understand user problems and needs, so that later applications developed are truly useful for users. For testing the prototype, the Usability Testing method is used, to assess the extent to which product can be used by certain users based on effectiveness, efficiency, and user satisfaction.